J.R.R. Tolkien : a biography - Carpenter, Humphrey (Boston : Houghton Mifflin, 2000)
A biography of J.R.R. Tolkien, creator of the fictional world of Middle-Earth, discussing his early life, his career as a scholar and teacher, his decision to write and the development of his work.
Reprint. Originally published: J.R.R. Tolkien. London : G. Allen & Unwin, 1977.
Includes index.
"Sources and acknowledgements": p. 276-279.
"The published writings of J.R.R. Tolkien": p. [266]-275.
Keywords: Tolkien, J. R. R. -- 1892-1973.; Authors, English -- 20th century -- Biography; Anglicists -- Great Britain -- Biography; Fantasy literature -- Authorship; Middle Earth (Imaginary place)